Safety Evaluation of Cervical Dorsal Instrumentation in Geriatric Patients: Experience at a Level 1 Center for Spinal Surgery—A Single Center Cohort Study - Shabo, Ehab; Brandecker, Simon; Rana, Shaleen; Bara, Gregor; Scorzin, Jasmin E.; Eichhorn, Lars; Vatter, Hartmut; Banat, Mohammed (Frontiers in Medicine, 2022)
Objective Dorsal instrumentation of the cervical spine is an established treatment in spinal surgery, but careful planning is required particularly in the case of older patients. This study evaluates early clinical outcomes in geriatric patients undergoing complex spinal surgery. Methods In this retrospective, single-center cohort study, we included all geriatric patients (aged ≥65 years) who underwent dorsal instrumentation between January 2013 and December 2020. We analyzed postoperative complications and the 30 days in-hospital mortality rate. Furthermore, the Charlson comorbidity index (CCI) and Clavien-Dindo grading system (CDG) were used to assess the patients comorbidity burden. Results In total, 153 patients were identified and included. The mean age of patients was 78 years (SD±7). Traumatic injury (53.6%) was the most common reason for surgery. 60.8% of the patients underwent dorsal instrumentation with 3 or more levels. The most common comorbidities were arterial hypertension (64%), Diabetes mellitus (22.2%), Coronary heart disease and Atrial fibrillation (19.6%). The most common adverse event was pneumonia (4%) and the most common surgery-related complication was wound infection (5.2%). Among patients categorized as high risk group for AE (CCI >5), 14.6% suffered a postoperative AE. In our univariate analysis, we found no risk factors for high rates of complications or mortality. Conclusion Our data demonstrate that older patients were at no significant risk of postoperative complications. The CCI/CDG may identify patients at higher risk for adverse events after dorsal instumentaion in the cervical spine surgery and it should become an essential component of stratification in this aging patient population.